Association of social support and religiosity with survival among women with breast cancer in a low-income population in the Southeastern United States - Ronald Fisa; Kabisa Mwala; Douglas DeMoulin; Violet Kayamba; Martha Shrubsole; Xiao-Ou Shu; Isaac Fwemba; Wilbroad Mutale; Loren Lipworth (BMC Public Health)
Abstract Background Large social networks have been associated with better overall survival after a breast cancer diagnosis in some but not all study populations. This study evaluated associations of social support and religiosity/spirituality with survival among Black and White women with breast cancer of largely low socioeconomic status in the United States (US). Methods The study used data from the prospective Southern Community Cohort Study, which enrolled approximately 86,000 adults in the southeastern US during 2002–2009. A total of 1,347 Black and White women with incident breast cancer were identified in the cohort and followed through December 2020 for mortality via linkage with the National Death Index. Exposures of interest were social support and religiosity obtained via baseline questionnaire, including number of close friends/relatives who can provide instrumental and emotional support, and frequency of attendance at religious services. Multivariable Cox regression models were used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for all-cause mortality in association with social support and religiosity. The models were tested for proportional hazards assumption using Schoenfeld residuals. Results Among the 1,347 women with breast cancer, 365 (27.1%) died during follow up. The participants were followed up for 17 years with a median follow-up time of 5 years. In all-cause mortality analyses, women who reported having 2 + relatives/friends for emotional support had a 20% reduced hazard of death compared to women with ≤ 1 relative/friend (HR = 0.80, 95% CI: 0.67–0.96) after adjusting for age at breast cancer diagnosis, race, time from cohort enrollment to diagnosis, income, education, marital status, insurance, and tumor hormone receptor status. Similarly, women reporting having 2 + people able to provide instrumental support (render assistance in an emergency or lend money) had a 25% (HR = 0.75, 95% CI: 0.59–0.95) reduced hazard of death compared to those who had ≤ 1. Frequent attendance at religious services/meetings was associated with reduced hazard of death compared to those who did not attend (HR = 0.60, CI: 0.41–0.89); addition of cancer stage in the models attenuated this association. Conclusions A large social support network and regular attendance at faith-based services were associated with better survival among women with breast cancer. This calls for incorporating appropriate interventions to cancer care such as social support groups to improve survival.